2016
DOI: 10.1038/srep37655
|View full text |Cite
|
Sign up to set email alerts
|

Extending standard testing period in honeybees to predict lifespan impacts of pesticides and heavy metals using dynamic energy budget modelling

Abstract: Concern over reported honeybee (Apis mellifera spp.) losses has highlighted chemical exposure as a risk. Current laboratory oral toxicity tests in A. mellifera spp. use short-term, maximum 96 hour, exposures which may not necessarily account for chronic and cumulative toxicity. Here, we use extended 240 hour (10 day) exposures to examine seven agrochemicals and trace environmental pollutant toxicities for adult honeybees. Data were used to parameterise a dynamic energy budget model (DEBtox) to further examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…[20, 21]) showed one or both chemicals to have an effect on survival at the tested concentrations. Controls containing only 50% w/v sucrose were included in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…[20, 21]) showed one or both chemicals to have an effect on survival at the tested concentrations. Controls containing only 50% w/v sucrose were included in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Improvement of research methods (sampling and measuring exposure) is also addressed by Benuszak et al (2017). Hesketh et al (2016) provide arguments for an increased exposure time (> 240 h) to better identify sublethal effects in honeybee toxicity test, the current standard being 96 h of exposure.…”
Section: Field Studiesmentioning
confidence: 99%
“…The data collected refers to 14 species of insects belonging to seven different taxonomic orders; among them is the brown planthopper (Nilaparvata lugens), a pest of rice crops and Frankiniella occidentalis, a pest of many flowers. In addition to the above, two tests using clothianidin showed that this compound followed Haber's rule when tested on honeybees (Apis mellifera) [44,45], whereas the same compound tested on bumblebees (Bombus terrestris) and mason bees (Osmia bicornis) appeared to show mainly dose-dependent toxicity [45]. One additional data set included acetamiprid, but this compound did not show time-dependent toxicity when tested on honeybees [46] (Table S2), perhaps because it is quickly metabolised [47].…”
Section: Terrestrial Organismsmentioning
confidence: 88%
“…The decrease in LC50 values (LC50) between the initial and final exposure times varies in the range 3 to 52 for all compounds, with notable exceptions for imidacloprid tested on female fruit flies (Drosophila melanogaster) and termites, which showed differences of 172 times over 8 days and 1167-3126 times over 21 days, respectively [44,46]. The result for imidacloprid on the fruit flies contrasts with previous tests that showed no time-dependent toxicity of this compound to the same species and equal 8-day testing period [47].…”
Section: Terrestrial Organismsmentioning
confidence: 99%
See 1 more Smart Citation